Analysis of the FinTech landscape in the Philippines - Francis Mark A. Quimba; Mark Anthony A. Barral; Jean Clarisse T. Carlos (Philippine Institute for Development Studies (PIDS), 2021)
FinTech in the Philippines has been gaining more attention in recent years, especially during the onset of the COVID-19 pandemic when lockdowns are prevalent and cashless payment methods are encouraged to limit exposure to health risks from face-to-face and cash-based transactions. Digital payments and digital engagements of both men and women have increased, and more and more bank and nonbank financial service providers have entered the digital space, providing more diversified financial products and services through various platforms. Despite these developments, however, the industry financial inclusion in the Philippines remains lagging behind compared to ASEAN neighbors. In addition, FinTech has faced concerns pertaining to the reliability and consistency not only of the systems but also of the regulations. With the financial sector being heavily disrupted by digitalization, there is more to look into than defining FinTech elements and considering it as just another service innovation. Defining the interplay across the stages of FinTech transformation does not seem to be well explored in the Philippines. This paper explores the state of the industry and investigates how to support the development of the ecosystem to ensure that FinTech helps in the achievement of the country's development goals. This paper finds that the Philippines has a strong FinTech industry as indicated by an increasing number of FinTechs (particularly in payments, lending, and banking technology verticals) and increasing capitalization. The FinTech industry can support the country's goals of financial inclusion but there needs to be an improvement in areas of availability of talent and credit for the sector.
Keywords: 330; Business models; FinTech; FinTech ecosystem; e-money; lending; financial inclusion; financial literacy